VR Smart Science Maze - Mohammad Amirul Shah, Mohamad Nasir (2023)
Effective learning methods in schools greatly impact the country's education system. Times are changing, many teachers are starting to realize that the old learning methods are still not enough to prove students' understanding of what they learn in school. Various approaches are taken by teachers in this country to help students understand learning. One of the learning approaches that can be applied to school students is playing while learning. Therefore, games with the theme of strategy and exploration were created to help teachers in ensuring student understanding. This game is also created using virtual reality technology, where students can see objects or things that are difficult to see in the real world but can be seen virtually. Throughout the game, students will be able to see displays with motifs and information in three dimensions (3D).